Integral Hematological Indices and Immunological Parameters in Acute Poisoning in Children - L. A. Kovalenko; G. N. Sukhodolova (Общая реаниматология, 2013)
Objective: to study the immune status in a group of children with acute chemical injury and to define the role of integral hematological parameters in the rapid evaluation of the functional state of the immune system. Subjects and methods. Ten patients aged 1 to 3 years with acute chemical poisoning were examined. They underwent immune status examination and clinical blood analysis with calculation of integral hematological parameters, by using the conventional formulas. Results. Within the first 24 hours of the disease, the children were found to have higher neutrophils, lower lymphocytes, and moderate monocytosis. Immunological studies revealed a reduction in total lymphocyte counts due to a decreased T-cell ratios. The level of B lymphocytes did not differ from the normal values, but at the same time there was impaired B-lymphocyte production of immunoglobulins. The absorbing capacity of neutrophils remained unchanged and oxygen-dependent cellular metabolism was enhanced. Conclusion. Immunological findings and integral hematological indices point to immune system functional changes forming in children via a systemic response to acute chemical poisoning. Key words: children, acute chemical injury, hematological indices, immune status.